PRAKTEK PEMBIAYAAN MUDHARABAH BERTINGKAT PADA BANK SYARIAH - Nizar Zikri Romdhani; Abdul Mujib (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2022)
This article is library research with research data sources sourced from primary and secondary sources. Primary data sources in the form of the Qur'an, hadith, laws, Fatwa DSN MUI, and others. While the secondary sources are fiqh books, books, journals, websites, and others. The data analysis method used is a qualitative-descriptive analysis method. The description of the data is divided into several stages, namely: Islamic banks in Indonesia, mudharabah in the perspective of fiqh muamalah, and the practice of financingÂ mudharabahÂ multilevel in Syariah Public Banks. Syariah Public Banks is an Islamic bank that in its activities provides services in payment traffic. Deposits in Sharia banks are investment funds based on mudarabah contracts or other.contracts that do not.conflict with Sharia principles. In practice, the fund manager (mudharib) invests money or repeats mudharabah, then there is a multilevel mudharabah contract which the fiqh scholars argue about its legal status, some allow it and some don't allow it. The research method is based on normative juridical and data collection methods that the authors use as a literature study. In this case, the Islamic bank is not only a mudharib, the Islamic bank is also a shahib al-mal. Based on the opinion of rajih among scholars, the law of conducting a multilevel mudharabah contract may be based on two considerations, namely urf considerations and the absolute concept of mudharabah.